Solid polymer electrolyte membrane, membrane electrode assembly, method for producing membrane electrode assembly, and water electrolysis device
By using a solid polymer containing ion exchange groups, a solid polymer electrolyte membrane containing platinum and cerium in the water electrolytic device, the problems of insufficient hydrogen penetration and chemical durability are solved, and the effects of excellent low gas permeability and chemical durability are achieved.
Patent Information
- Application Number
- CN202380065467.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-29
AI Technical Summary
The existing solid polymer electrolyte membrane has a problem of hydrogen penetration in the water electrolytic device, which leads to a decrease in hydrogen recovery efficiency, and fluoropolymers are prone to decomposition during operation, and lack of chemical durability.
A solid polymer electrolyte membrane containing fluoropolymers with ion exchange groups, platinum and cerium is used to inhibit hydrogen penetration by heavy presence of platinum and cerium in the membrane, and quenching OH radicals by cerium ions to improve chemical durability.
A solid polymer electrolyte membrane with excellent low gas permeability and chemical durability is achieved, reducing the risks of hydrogen penetration and fluoropolymer decomposition, and improving the performance of the water electrolytic device.
Smart Images

Figure CN119908016A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid polymer electrolyte membrane, a membrane electrode assembly, a method for manufacturing the membrane electrode assembly, and a water electrolysis device. Background Art
[0002] From the perspective of power-to-gas, that is, converting surplus electricity into gas for storage and utilization, the use of solid polymer water electrolysis devices (PEM water electrolysis devices) is being studied.
[0003] For example, Patent Document 1 discloses a solid polymer water electrolysis device having a membrane electrode assembly including: an anode and a cathode each having a catalyst layer; and a solid polymer electrolyte membrane disposed between the anode and the cathode.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2022 / 050363 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] In recent years, further performance improvement of water electrolysis devices is required, specifically, reduction of hydrogen penetration (crossover) is required. Here, hydrogen penetration refers to the movement of hydrogen generated at the cathode to the anode side through the solid polymer electrolyte membrane in the water electrolysis device. If hydrogen penetration occurs, there is a problem of reduced hydrogen recovery efficiency. Therefore, it is required that the solid polymer electrolyte membrane can suppress the penetration of hydrogen generated in the system, that is, low gas permeability.
[0009] In addition, when a solid polymer electrolyte membrane is used in a water electrolysis device, the fluorinated polymer in the solid polymer electrolyte membrane may be decomposed by compounds (eg, hydrogen peroxide) generated in the system during operation. Therefore, a solid polymer electrolyte membrane with excellent chemical durability is required.
[0010] The present inventors evaluated a water electrolysis device having a solid polymer electrolyte membrane as described in Patent Document 1 and found that there is room for improvement in at least one of low gas permeability and chemical durability of the solid polymer electrolyte membrane.
[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a solid polymer electrolyte membrane having low gas permeability and excellent chemical durability, a membrane electrode assembly, a method for producing the membrane electrode assembly, and a water electrolysis device.
[0012] Solutions for solving problems
[0013] The present inventors have conducted intensive studies on the above-mentioned subject and have found that the desired effect can be obtained by using a solid polymer electrolyte membrane comprising a fluorinated polymer having an ion exchange group, a platinum-containing material, at least one of cerium ions and a salt thereof, and a woven fabric, thereby completing the present invention.
[0014] That is, the inventors have found that the above-mentioned problems can be solved by the following configuration.
[0015] [1] A solid polymer electrolyte membrane comprising: a fluorine-containing polymer having an ion exchange group, a platinum-containing material, cerium, and a woven fabric, wherein the cerium is present in the solid polymer electrolyte membrane in the form of at least one of an ion and a salt.
[0016] [2] The polymer electrolyte membrane according to [1], wherein the platinum-containing substance and the cerium are concentrated on one surface side of the polymer electrolyte membrane.
[0017] [3] The solid polymer electrolyte membrane according to [1] or [2], wherein the ion exchange capacity of the fluorinated polymer is 0.90 to 2.00 milliequivalents / g dry resin.
[0018] [4] The solid polymer electrolyte membrane according to any one of [1] to [3], wherein the platinum-containing substance is supported on a carrier.
[0019] [5] The polymer electrolyte membrane according to any one of [1] to [4], wherein the ion exchange group of the fluorinated polymer is a sulfonic acid type functional group.
[0020] [6] The solid polymer electrolyte membrane according to any one of [1] to [5], wherein the fluorinated polymer comprises at least one unit selected from the group consisting of a unit represented by formula (1-3) and a unit represented by formula (1-4).
[0021] In the formula (1-3) and formula (1-4) described below, R f1 is a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f2 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f3 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, r is 0 or 1, m is 0 or 1, and M is each independently a hydrogen atom, an alkali metal or a quaternary ammonium cation.
[0022] [7] The polymer electrolyte membrane according to any one of [1] to [6], wherein the woven fabric is made of a material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyetheretherketone and polyphenylene sulfide.
[0023] [8] The solid polymer electrolyte membrane according to any one of [1] to [7], wherein the solid polymer electrolyte membrane comprises a first electrolyte layer and a second electrolyte layer,
[0024] The first electrolyte layer includes the platinum-containing substance and the cerium.
[0025] The second electrolyte layer has a lower concentration of the platinum-containing substance and the cerium than the first electrolyte layer, or does not contain the platinum-containing substance and the cerium.
[0026] [9] A solid polymer electrolyte membrane according to any one of [1] to [8], wherein the thickness of the solid polymer electrolyte membrane is greater than 80 μm, and the ratio of the amount of the cerium substance to the amount of the ion exchange group of the fluorinated polymer is greater than 0.24 mol%.
[0027]
[10] A membrane electrode assembly, comprising:
[0028] The solid polymer electrolyte membrane according to any one of [1] to [9];
[0029] a cathode catalyst layer disposed on one side of the solid polymer electrolyte membrane, and
[0030] An anode catalyst layer is disposed on the other surface of the solid polymer electrolyte membrane.
[0031]
[11] A water electrolysis device, characterized in that it has:
[0032]
[10] The membrane electrode assembly described in claim 1;
[0033] a power supply unit connected to the cathode catalyst layer side and the anode catalyst layer side of the membrane electrode assembly; and
[0034] A water supply unit supplies water to the anode catalyst layer side.
[0035]
[12] A method for manufacturing a membrane electrode assembly, the membrane electrode assembly comprising: a solid polymer electrolyte membrane described in any one of [1] to [9], a cathode catalyst layer and an anode catalyst layer, wherein in the manufacturing method, the cathode catalyst layer is formed on one side of the solid polymer electrolyte membrane, and the anode catalyst layer is formed on the other side of the solid polymer electrolyte membrane.
[0036] Effects of the Invention
[0037] According to the present invention, a solid polymer electrolyte membrane having low gas permeability and excellent chemical durability, a membrane electrode assembly, a method for producing the membrane electrode assembly, and a water electrolysis device can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic cross-sectional view of an electrolyte membrane for explaining a state in which a platinum-containing substance and cerium are present in a heavy manner.
[0039] Figure 2 This is a cross-sectional view schematically showing an example of the membrane electrode assembly of the present invention.
[0040] Figure 3 This is a cross-sectional view schematically showing another example of the membrane electrode assembly of the present invention. DETAILED DESCRIPTION
[0041] The definitions of the following terms apply throughout the entire specification and claims unless otherwise specified.
[0042] The "ion exchange group" refers to a group that can exchange at least a part of the ions contained in the group for other ions, and examples thereof include the following sulfonic acid type functional group and carboxylic acid type functional group.
[0043] The "sulfonic acid type functional group" refers to a sulfonic acid group (-SO3H) or a sulfonate group. Here, as a form of a sulfonate group, for example, (-SO3 - )Ma + 、(-SO3 - )2Mb 2+ , and (-SO3 - )3Mc 3+ (Among them, Ma + is an alkali metal ion or a quaternary ammonium cation, Mb 2+ is a divalent metal ion, Mc 3+ It should be noted that when there are two ligands, the number of ion exchange groups is counted as 2, and when there are three ligands, the number of ion exchange groups is counted as 3.
[0044] The "carboxylic acid type functional group" refers to a carboxylic acid group (-COOH) or a carboxylate group. Here, as a form of a carboxylate group, for example, (-CO - )Ma + 、(-COO - )2Mb 2+ , and (-COO - )3Mc 3+ Can be cited (among which, Ma + is an alkali metal ion or a quaternary ammonium cation, Mb 2+ is a divalent metal ion, Mc3+ It should be noted that when there are two ligands, the number of ion exchange groups is counted as 2, and when there are three ligands, the number of ion exchange groups is counted as 3.
[0045] "Precursor membrane" refers to a membrane comprising a polymer having groups that can be converted into ion exchange groups.
[0046] The "group convertible into an ion exchange group" refers to a group convertible into an ion exchange group by a treatment such as a hydrolysis treatment or an acidification treatment.
[0047] The "group convertible into a sulfonic acid type functional group" refers to a group convertible into a sulfonic acid type functional group by a treatment such as a hydrolysis treatment or an acidification treatment.
[0048] The "group convertible into a carboxylic acid type functional group" refers to a group convertible into a carboxylic acid type functional group by a known treatment such as a hydrolysis treatment or an acidification treatment.
[0049] The "unit" in a polymer refers to an atomic group derived from one molecule of a monomer formed by polymerization of the monomer. The unit may be an atomic group directly formed by a polymerization reaction, or an atomic group in which a part of the atomic group is converted into another structure by treating a polymer obtained by a polymerization reaction.
[0050] The numerical range represented by "to" refers to a range including the numerical values recorded before and after "to" as the lower limit and the upper limit. In the numerical range recorded in stages in this specification, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.
[0051] [Electrolyte membrane]
[0052] The solid polymer electrolyte membrane of the present invention (hereinafter, also referred to as "electrolyte membrane") is the following solid polymer electrolyte membrane, which comprises: a fluorinated polymer having an ion exchange group (hereinafter, also referred to as "fluorinated polymer (I)"), a platinum-containing material, cerium and a woven fabric, wherein the cerium is present in the solid polymer electrolyte membrane in the form of at least one of an ion and a salt. It should be noted that in this specification, when referred to as "cerium", it refers to both "cerium ions" and "salts of cerium ions".
[0053] When the electrolyte membrane of the present invention is applied to a water electrolysis device, it is presumed that the hydrogen generated on the cathode side reacts with the oxygen generated on the anode side on the platinum-containing material contained in the electrolyte membrane to form water, thereby suppressing the movement of hydrogen to the anode side (hydrogen penetration). For such reasons, it is believed that the electrolyte membrane of the present invention has excellent low gas permeability.
[0054] In addition, when the electrolyte membrane of the present invention is applied to a water electrolysis device, it is presumed that the OH radicals generated by hydrogen peroxide generated in the system during operation are quenched by cerium ions contained in the electrolyte membrane or cerium ions dissociated from cerium salts, resulting in the inhibition of decomposition of the fluorinated polymer (I). For this reason, it is believed that the chemical durability of the electrolyte membrane of the present invention is also excellent.
[0055] In addition, when the electrolyte membrane of the present invention is applied to a water electrolysis device, the hydrogen generated on the cathode side reacts with the oxygen generated on the anode side on the platinum-containing material contained in the electrolyte membrane to form water, thereby reducing the amount of hydrogen peroxide generated, and the platinum-containing material itself can decompose hydrogen peroxide, thereby reducing the amount of OH radicals generated. For this reason, the electrolyte membrane of the present invention is also considered to have excellent chemical durability.
[0056] The electrolyte membrane may be a single-layer structure or a multi-layer structure. Specific forms of the electrolyte membrane as a multi-layer structure include a form in which a plurality of electrolyte layers containing at least one of platinum and cerium with different contents are stacked, and a form in which a plurality of electrolyte membranes with different ion exchange capacities are stacked.
[0057] The platinum-containing substance and cerium contained in the electrolyte membrane may be dispersed in the entire electrolyte membrane or may be concentrated on one surface side of the electrolyte membrane. It is preferred that at least one of the platinum-containing substance and cerium is concentrated on one surface side of the electrolyte membrane, and it is more preferred that the platinum-containing substance and cerium (i.e., both the platinum-containing substance and cerium) are concentrated on one surface side of the electrolyte membrane.
[0058] When the platinum-containing substance and cerium are concentrated on one surface side of the electrolyte membrane, the one surface side of the electrolyte membrane becomes hard, so that when the electrolyte membrane is used in a water electrolysis device, the electrolyte membrane can be prevented from wrinkling.
[0059] In addition, when the electrolyte membrane is applied to a water electrolysis device, it is preferred to arrange the surface of the electrolyte membrane on the side where the platinum-containing substance is more heavily present on the anode side in order to further suppress the occurrence of hydrogen crossover. In this case, the catalyst contained in the catalyst layer of the anode preferably contains iridium oxide in order to achieve the above-mentioned better effect.
[0060] In the present specification, "platinum-containing substances are concentrated on one surface side of the electrolyte membrane" means that the concentration of platinum-containing substances in the region from one surface of the electrolyte membrane (hereinafter also referred to as "surface A") to a specified depth position (hereinafter also referred to as "depth position B") before reaching the other surface (hereinafter also referred to as "surface C") is higher than the concentration of platinum-containing substances in the region from surface C to depth position B.
[0061] Furthermore, “cerium is concentrated on one surface side of the electrolyte membrane” means that the concentration of cerium in the region from the surface A to the depth position B is higher than the concentration of cerium in the region from the surface C to the depth position B.
[0062] In addition, “platinum-containing substances and cerium are concentrated on one surface side of the electrolyte membrane” means that the concentration of platinum-containing substances in the region from surface A to depth position B is higher than the concentration of platinum-containing substances in the region from surface C to depth position B, and the concentration of cerium in the region from surface A to depth position B is higher than the concentration of cerium in the region from surface C to depth position B.
[0063] Here, as one of the preferred modes for the platinum-containing substance and the cerium ions to be concentrated on one surface side of the electrolyte membrane, the following mode can be cited: the depth position B from the surface A to 50% of the membrane thickness of the electrolyte membrane 50 The concentration of the platinum-containing material in the region from the surface C to the depth position B is 50 The concentration of platinum-containing substances in the region from surface A to depth B is high. 50 The concentration of cerium in the region from surface C to depth B is 50 The concentration of cerium ions in the region up to 100 Å is high.
[0064] use Figure 1 The example will be specifically described with respect to the state where “the platinum-containing substance and cerium are present more heavily on one surface side of the electrolyte membrane”. Figure 1 It is a schematic cross-sectional view of an electrolyte membrane for explaining a state in which a platinum-containing substance and cerium are present in a heavy manner.
[0065] exist Figure 1 In FIG. 1 , the electrolyte membrane 1 has a surface A1 as one surface and a surface C1 as the other surface. The depth position B1 indicates the distance T from the surface A1 to the surface C1. X The length of the position.
[0066] The shortest distance T1 from the surface A1 to the surface C1 of the electrolyte membrane 1 corresponds to the thickness of the electrolyte membrane 1. X is X% of the distance T1. XWhen the length is 20% of the distance T1 , the depth position B1 corresponds to a position corresponding to 20% of the thickness (distance T1 ) of the electrolyte membrane 1 from the surface A1 of the electrolyte membrane 1 .
[0067] The region X indicates a region from the surface A1 to the depth position B1 , and the region Y indicates a region from the surface C1 to the depth position B1 .
[0068] In addition, when the surface of the electrolyte membrane 1 has irregularities, the above-mentioned distances are measured with reference to the position where the thickness of the electrolyte membrane 1 is the smallest.
[0069] exist Figure 1 When the concentration of the platinum-containing substance in region X is higher than that in region Y, and the concentration of cerium in region X is higher than that in region Y, it can be said that "the platinum-containing substance and cerium are concentrated on one surface side of the electrolyte membrane".
[0070] For the platinum-containing substance and cerium contained in the electrolyte membrane, from the aspect of more excellent effects of the present invention, it is preferred that they exist from one surface of the electrolyte membrane to a position corresponding to 25% of the thickness of the electrolyte membrane, more preferably from one surface of the electrolyte membrane to a position corresponding to 20% of the thickness of the electrolyte membrane, further preferably from one surface of the electrolyte membrane to a position corresponding to 15% of the thickness of the electrolyte membrane, and particularly preferably from one surface of the electrolyte membrane to a position corresponding to 10% of the thickness of the electrolyte membrane. It is further preferred that the platinum-containing substance and cerium contained in the electrolyte membrane exist only to these film thicknesses.
[0071] The positions where the platinum-containing substance and cerium exist in the electrolyte membrane can be determined by element distribution using, for example, an energy dispersive X-ray analyzer (product name: "QUANTAX FlatQUAD", manufactured by Bruker Corporation).
[0072] Based on the obtained element distribution, the above-mentioned distance Tx can be calculated.
[0073] As an example of a method for making platinum-containing substances and cerium more concentrated on one surface side of an electrolyte membrane, there is a method of stacking a first electrolyte layer and a second electrolyte layer to obtain an electrolyte membrane, wherein the first electrolyte layer contains platinum-containing substances and cerium, and the concentration of platinum-containing substances and cerium in the second electrolyte layer is lower than that in the first electrolyte layer, or the second electrolyte layer does not contain platinum-containing substances and cerium.
[0074] As another method, the following method can be mentioned: a solution containing platinum ions and a solution containing cerium ions are impregnated from one surface of an electrolyte membrane that does not contain platinum-containing substances and cerium, so that platinum-containing substances and cerium are contained from one surface of the electrolyte membrane to a predetermined depth position of the electrolyte membrane.
[0075] The electrolyte membrane preferably contains substantially no thickener in view of high membrane resistance. The electrolyte membrane contains substantially no thickener means that the content of the thickener is 0.1 mass % or less, preferably 0.01 mass % or less, and more preferably 0 mass % relative to the total mass of the electrolyte membrane.
[0076] Specific examples of the thickener will be described later.
[0077] The thickness of the electrolyte membrane is preferably 40 μm or more, more preferably 60 μm or more, further preferably 70 μm or more, particularly preferably 80 μm or more, and preferably 400 μm or less, more preferably 300 μm or less, further preferably 200 μm or less, particularly preferably 100 μm or less. It should be noted that, when the electrolyte membrane has a multilayer structure, the thickness of the electrolyte membrane refers to the total thickness of each layer.
[0078] When the electrolyte membrane has a multilayer structure and has the above-mentioned first electrolyte layer and the above-mentioned second electrolyte layer, the ratio of the thickness of the first electrolyte layer to the thickness of the second electrolyte layer (thickness of the first electrolyte layer / thickness of the second electrolyte layer) is preferably greater than 0.02, more preferably greater than 0.05, further preferably greater than 0.11, particularly preferably greater than 0.16, most preferably greater than 0.32, and in addition, it is preferably less than 0.50, more preferably less than 0.40.
[0079] The thickness of the electrolyte membrane is measured using an enlarged image (e.g., 100 times) of a cross section of the electrolyte membrane taken using an optical microscope (product name "BX-51", manufactured by Olympus Corporation). It should be noted that when there are concave and convex portions on the surface of the electrolyte membrane, the thickness of the concave portion at 10 points in the electrolyte membrane and the thickness of the convex portion at 10 points in the electrolyte membrane are measured, and the arithmetic mean of the thickness of the total 20 points is taken as the thickness of the electrolyte membrane. Among them, in the case where the convex portion includes yarn constituting the woven fabric, the thickness of the convex portion is the value obtained by subtracting the thickness of the yarn present in the convex portion.
[0080] <Weaving>
[0081] The fabric plays a role in improving the dimensional stability, strength, and handling properties of the electrolyte membrane.
[0082] The opening ratio of the woven fabric is preferably 50% or more, more preferably 55% or more, further preferably 60% or more, and particularly preferably 70% or more, from the viewpoint of further reducing the electrolysis voltage.
[0083] From the viewpoint of achieving better strength of the membrane electrode assembly, the upper limit of the opening ratio of the woven fabric is preferably 90% or less, particularly preferably 80% or less.
[0084] The open area ratio of the woven fabric is calculated by the following formula (ε) based on the average diameter R1 of the yarns constituting the woven fabric and the average interval P1 between adjacent yarns (hereinafter also referred to as “pitch P1”) among the yarns constituting the woven fabric.
[0085] Here, the average diameter R1 of the yarn refers to the arithmetic mean of the diameters of 10 different yarns selected at random based on the magnified image (e.g., 100 times) of the woven surface obtained using a microscope. In addition, the pitch P1 refers to the arithmetic mean of 10 points at intervals of 10 points selected at random based on the magnified image (e.g., 100 times) of the woven surface obtained using a microscope.
[0086] Opening ratio of fabric (%) = [P1 / (P1+R1)] 2 ×100(ε)
[0087] The denier of the yarn constituting the woven fabric is preferably 2 or more, more preferably 10 or more, and particularly preferably 15 or more, from the viewpoint of achieving better strength and dimensional stability of the membrane electrode assembly.
[0088] From the viewpoint of being able to further reduce the electrolytic voltage, the upper limit of the denier of the yarn constituting the woven fabric is preferably 60 or less, more preferably 50 or less, and particularly preferably 20 or less.
[0089] In addition, the denier is a value expressing the mass of 9000 m of yarn in grams (g / 9000 m).
[0090] From the perspective of excellent strength and dimensional stability of the membrane electrode assembly, the density of the yarn constituting the woven fabric is preferably 50 yarns / inch or more, more preferably 70 yarns / inch or more, and particularly preferably 90 yarns / inch or more. From the perspective of further reducing the electrolysis voltage, the density of the yarn is preferably 200 yarns / inch or less, more preferably 150 yarns / inch or less, and particularly preferably 100 yarns / inch or less.
[0091] The yarn constituting the woven fabric may be composed of either a monofilament composed of one filament or a multifilament composed of two or more filaments, but is preferably composed of a monofilament.
[0092] From the perspective of better durability of the yarn, the yarns constituting the woven fabric are preferably each independently composed of a material selected from the group consisting of polytetrafluoroethylene (hereinafter also referred to as "PTFE"), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (hereinafter also referred to as "PFA"), polyetheretherketone (hereinafter also referred to as "PEEK"), and polyphenylene sulfide (hereinafter also referred to as "PPS").
[0093] The yarn constituting the woven fabric is preferably composed of slit yarns from the viewpoint of better durability and strength of the yarn.
[0094] When the material constituting the woven fabric is PTFE, the weight per unit area of the woven fabric is preferably 20 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 Above, preferably 30g / m 2 More than, preferably 40g / m 2 the following.
[0095] When the material constituting the woven fabric is PFA, the weight per unit area of the woven fabric is preferably 10 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 More than, preferably 30g / m 2 Below, more preferably 20g / m 2 the following.
[0096] When the material constituting the woven fabric is PEEK, the weight per unit area of the woven fabric is preferably 5 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 More than, preferably 40g / m 2 Below, more preferably 30g / m 2 the following.
[0097] When the material constituting the woven fabric is PPS, the weight per unit area of the woven fabric is preferably 5 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 More than, preferably 40g / m 2 More preferably 30 g / m 2 the following.
[0098] The content of the woven fabric is preferably 3 mass % or more, more preferably 5 mass % or more, and is preferably 50 mass % or less, more preferably 40 mass % or less, and further preferably 30 mass % or less, based on the total mass of the electrolyte membrane.
[0099] <Fluoropolymer (I)>
[0100] The ion exchange capacity of the fluoropolymer (I) is preferably 0.90 milliequivalent / g dry resin or more, more preferably greater than 1.10 milliequivalent / g dry resin, further preferably 1.15 milliequivalent / g dry resin or more, particularly preferably 1.20 milliequivalent / g dry resin or more, and most preferably 1.25 milliequivalent / g dry resin or more, from the viewpoint of being able to further reduce the electrolysis voltage when used in a water splitting device.
[0101] The ion exchange capacity of the fluoropolymer (I) is preferably 2.00 meq / g dry resin or less, more preferably 1.50 meq / g dry resin or less, further preferably 1.43 meq / g dry resin or less, from the viewpoint of the strength of the membrane electrode assembly when containing water.
[0102] The fluorinated polymer (I) may be used alone or in the form of a stack or a mixture of two or more.
[0103] The electrolyte membrane may contain polymers other than the fluoropolymer (I), and the polymer in the electrolyte membrane is preferably substantially composed of the fluoropolymer (I). Substantially composed of the fluoropolymer (I) means that the content of the fluoropolymer (I) is 95% by mass or more relative to the total mass of the polymers in the electrolyte membrane. As the upper limit of the content of the fluoropolymer (I), 100% by mass relative to the total mass of the polymers in the electrolyte membrane can be cited.
[0104] Specific examples of other polymers than the fluorinated polymer (I) include one or more polyazole compounds selected from the group consisting of polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and containing oxygen atoms and / or sulfur atoms.
[0105] Specific examples of the polyazole compound include polyimidazole compounds, polybenzimidazole compounds, polybenzbisimidazole compounds, polybenzoxazole compounds, polyoxazole compounds, polythiazole compounds, and polybenzothiazole compounds.
[0106] In addition, from the viewpoint of oxidation resistance of the electrolyte membrane, other polymers include polyphenylene sulfide resin and polyphenylene ether resin.
[0107] The fluorinated polymer (I) has an ion exchange group. Specific examples of the ion exchange group include sulfonic acid functional groups and carboxylic acid functional groups. Sulfonic acid functional groups are preferred because they can further reduce the electrolysis voltage when the electrolyte membrane is used in a water electrolysis device.
[0108] Hereinafter, an embodiment of the fluorinated polymer having a sulfonic acid type functional group (hereinafter also referred to as “fluorinated polymer (S)”) will be described in detail.
[0109] The fluorinated polymer (S) preferably contains a unit based on a fluorinated olefin and a unit having a sulfonic acid type functional group and a fluorine atom.
[0110] As the fluorinated olefin, for example, a fluorinated olefin having 2 to 3 carbon atoms and having one or more fluorine atoms in the molecule can be cited. Specific examples of the fluorinated olefin include tetrafluoroethylene (hereinafter also referred to as "TFE"), chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride, and hexafluoropropylene. Among them, TFE is preferred from the perspectives of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtained fluorinated polymer (S).
[0111] The fluorinated olefins may be used alone or in combination of two or more.
[0112] As the unit having a sulfonic acid type functional group and a fluorine atom, a unit represented by formula (1) is preferred.
[0113] Formula (1) -[CF2-CF(-L-(SO3M) n )]-
[0114] L is an n+1-valent perfluorocarbon group which may contain an etheric oxygen atom.
[0115] The etheric oxygen atom may be located at the terminal of the perfluorocarbon group or between carbon atoms.
[0116] The number of carbon atoms in the n+1-valent perfluorocarbon group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0117] L is preferably an n+1-valent perfluoroaliphatic hydrocarbon group optionally containing an etheric oxygen atom, more preferably a divalent perfluoroalkylene group optionally containing an etheric oxygen atom in which n=1 is an embodiment, or a trivalent perfluoroaliphatic hydrocarbon group optionally containing an etheric oxygen atom in which n=2 is an embodiment.
[0118] The divalent perfluoroalkylene group may be linear or branched.
[0119] M is a hydrogen atom, an alkali metal or a quaternary ammonium cation. When M is a plurality of groups, the plurality of groups may be the same or different.
[0120] n is 1 or 2.
[0121] The unit represented by formula (1) is preferably a unit represented by formula (1-1), a unit represented by formula (1-2), a unit represented by formula (1-3), or a unit represented by formula (1-4).
[0122] Formula (1-1) -[CF2-CF(-OR f1 -SO3M)]-
[0123] Formula (1-2) -[CF2-CF(-R f1 -SO3M)]-
[0124] Formula (1-3)
[0125] Formula (1-4)
[0126] R f1 The perfluoroalkylene group is a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0127] R f2 The perfluoroalkylene group is a single bond or may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0128] R f3 The perfluoroalkylene group is a single bond or may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0129] r is 0 or 1.
[0130] m is 0 or 1.
[0131] M is each independently a hydrogen atom, an alkali metal or a quaternary ammonium cation.
[0132] As the unit represented by the formula (1-1) and the unit represented by the formula (1-2), the unit represented by the formula (1-5) is more preferable.
[0133] Formula (1-5) -[CF2-CF(-(CF2) x -(OCF2CFY) y -O-(CF2) z -SO3M)] -x is 0 or 1, y is an integer of 0 to 2, z is an integer of 1 to 4, and Y is F or CF3. M is as described above.
[0134] Specific examples of the unit represented by formula (1-1) include the following units: w in the formula is an integer of 1 to 8, and x is an integer of 1 to 5. M in the formula has the same meaning as described above.
[0135] -[CF2-CF(-O-(CF2) w -SO3M)]-
[0136] -[CF2-CF(-O-CF2CF(CF3)-O-(CF2) w -SO3M)]-
[0137] -[CF2-CF(-(O-CF2CF(CF3)) x -SO3M)]-
[0138] Specific examples of the unit represented by formula (1-2) include the following units: w in the formula is an integer of 1 to 8. M in the formula has the same meaning as described above.
[0139] -[CF2-CF(-(CF2) w -SO3M)]-
[0140] -[CF2-CF(-CF2-O-(CF2) w -SO3M)]-
[0141] As the unit represented by the formula (1-3), the unit represented by the formula (1-3-1) is preferred. M in the formula has the same meaning as described above.
[0142] Formula (1-3-1)
[0143] R f4 is a linear perfluoroalkylene group having 1 to 6 carbon atoms, R f5 It is a single bond or a linear perfluoroalkylene group having 1 to 6 carbon atoms which may contain an oxygen atom between carbon atoms. r and M are as defined above.
[0144] Specific examples of the unit represented by formula (1-3-1) include the following.
[0145]
[0146] As the unit represented by formula (1-4), the unit represented by formula (1-4-1) is preferred. f1 , R f2 and M are defined as above.
[0147] Formula (1-4-1)
[0148] Specific examples of the unit represented by formula (1-4-1) include the following.
[0149]
[0150] The unit having a sulfonic acid type functional group and a fluorine atom may be used alone or in combination of two or more.
[0151] The fluorinated polymer (I) may contain units based on other monomers in addition to the units based on the fluorinated olefin and the units having a sulfonic acid type functional group and a fluorine atom.
[0152] Specific examples of other monomers include CF2=CFR f6 (Among them, R f6It is a perfluoroalkyl group having 2 to 10 carbon atoms. )CF2=CF-OR f7 (Among them, R f7 It is a perfluoroalkyl group having 1 to 10 carbon atoms. )CF2=CFO(CF2) v CF=CF2 (wherein v is an integer from 1 to 3).
[0153] The content of the units based on other monomers is preferably at most 30 mass % based on all the units in the fluorinated polymer (I) in order to maintain the ion exchange performance.
[0154] The content of the fluorinated polymer (I) is preferably 95 to 100% by mass based on the total mass of the electrolyte membrane.
[0155] <Platinum-containing substances>
[0156] The platinum-containing material may contain platinum atoms. Specific examples of the platinum-containing material include platinum itself, platinum oxides, composite metal oxides containing platinum, and platinum alloys.
[0157] Specific examples of the composite oxide containing platinum include: x Pt3O4 (M is at least one metal atom selected from the group consisting of Li, Na, Mg, Ca, Zn, Cd, Co, Ni, Mn, Cu, Ag, Bi and Ce, and x is greater than 0 and less than 1.).
[0158] Specific examples of the platinum alloy include alloys containing at least one metal selected from the group consisting of transition metals and noble metals other than platinum and containing platinum.
[0159] As specific examples of the shape of the platinum-containing material, a granular shape and a flake shape can be cited. When the platinum-containing material is granular, the platinum-containing material can be a core-shell type particle. As an example of a core-shell type particle, a particle having a core of carbon or a metal other than platinum and a shell containing platinum atoms can be cited.
[0160] When the platinum-containing material is in granular form, the average particle size (D50) of the platinum-containing material is preferably 1 nm or more, more preferably 10 nm or more, further preferably 100 nm or more, and preferably 10000 nm or less, more preferably 5000 nm or less, further preferably 3000 nm or less.
[0161] The average particle size of the platinum-containing substance is the cumulative 50% particle size (D50) based on volume obtained by dispersing the dispersion containing the platinum-containing substance using a particle size distribution analyzer. The detailed measurement conditions are described in the examples.
[0162] When the electrolyte membrane is a single-layer structure, the average 2The mass of the platinum-containing substance in the electrolyte membrane is preferably 0.010 mg / cm 2 More preferably 0.030 mg / cm 2 More preferably 0.040 mg / cm 2 Above, preferably 0.050 mg / cm 2 Below. The mass of platinum-containing material is 0.030 mg / cm 2 When the mass of the platinum-containing material is 0.050 mg / cm 2 When the electrolysis voltage is less than 0.1, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0163] When the electrolyte membrane has a multilayer structure, the average 1 cm of at least one electrolyte layer (preferably the first electrolyte layer) contained in the electrolyte membrane 2 The mass of the platinum-containing substance in the electrolyte layer is preferably 0.010 mg / cm 2 More preferably 0.015 mg / cm 2 More preferably, 0.030 mg / cm 2 Above, particularly preferably 0.040 mg / cm 2 Above, preferably 0.050 mg / cm 2 Below. The mass of platinum-containing material is 0.030 mg / cm 2 When the mass of the platinum-containing material is 0.050 mg / cm 2 When the electrolysis voltage is less than 0.1, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0164] When the electrolyte membrane is a single-layer structure, the mass ratio of the platinum-containing substance to the fluoropolymer (I) in the electrolyte membrane (mass of the platinum-containing substance / mass of the fluoropolymer (I)) is preferably 0.0005 to 0.0040. When the mass ratio is 0.0005 or more, the occurrence of hydrogen penetration can be further suppressed. When the mass ratio is 0.0040 or less, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0165] In the case where the electrolyte membrane has a multilayer structure, the mass ratio of the platinum-containing substance to the fluoropolymer (I) in at least one electrolyte layer (preferably the first electrolyte layer described above) contained in the electrolyte membrane (mass of the platinum-containing substance / mass of the fluoropolymer (I)) is preferably 0.005 or more, more preferably 0.007 or more, further preferably 0.014 or more, and preferably 0.024 or less. When the mass ratio is 0.005 or more, the occurrence of hydrogen penetration can be further suppressed. When the mass ratio is 0.024 or less, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0166] The platinum-containing substance may be supported on a carrier. Specific examples of the carrier include carbon carriers such as carbon black powder, graphitized carbon, carbon fiber, and carbon nanotube.
[0167] When the platinum-containing material is loaded on a carrier, the loading amount of the platinum-containing material is preferably 10 mass % or more, more preferably 20 mass % or more, further preferably 30 mass % or more, and preferably 50 mass % or less, relative to the total mass of the platinum-containing material and the carrier.
[0168] When the platinum-containing substance is loaded on a carrier, the mass ratio of the fluorinated polymer (I) to the carrier loading the platinum-containing substance (mass of the fluorinated polymer (I) / mass of the carrier) is preferably 10.0 or more, more preferably 30.0 or more, further preferably 60.0 or more, and preferably 500 or less.
[0169] <Cerium>
[0170] Cerium exists in the electrolyte membrane in the form of at least one of ions and salts.
[0171] The cerium ion is preferably a trivalent cerium ion.
[0172] Specific examples of the cerium salt include salts formed of ion exchange groups of a fluorinated polymer and cerium ions.
[0173] With regard to the ratio of the amount of cerium substance in the electrolyte membrane to the amount of substance of the ion exchange group of the fluorinated polymer (I), from the perspective of achieving a more excellent effect of the present invention, it is preferably 0.1 mol% or more, more preferably 0.17 mol% or more, further preferably 0.24 mol% or more, particularly preferably 0.50 mol% or more, and most preferably 0.70 mol% or more. In addition, it is preferably 5.0 mol% or less, more preferably 3.8 mol% or less, further preferably 2.1 mol% or less. From the perspective of being able to further suppress the occurrence of curling (warping) of the electrolyte membrane, it is particularly preferably 1.3 mol% or less.
[0174] From the viewpoint of particularly excellent effects of the present invention, the electrolyte membrane preferably has a thickness of 80 μm or more and a ratio of the amount of cerium to the amount of ion exchange groups of the fluorinated polymer (I) of at least 0.24 mol %.
[0175] <Method for producing electrolyte membrane>
[0176] As an example of a method for producing an electrolyte membrane, the following method can be mentioned.
[0177] First, in a polymer (hereinafter also referred to as "fluorinated polymer (I')") of a fluorinated monomer having a group convertible into an ion-exchange group (hereinafter also referred to as a fluorinated monomer (I')), the group convertible into an ion-exchange group is converted into an ion-exchange group to obtain a fluorinated polymer (I).
[0178] Next, the woven fabric is impregnated with the dispersion in which the fluorinated polymer (I) and the platinum-containing material are dispersed, and dried to obtain an electrolyte membrane comprising the fluorinated polymer (I), the platinum-containing material and the woven fabric.
[0179] Next, the electrolyte membrane obtained as described above is immersed in a solution containing a water-soluble cerium salt and then dried to obtain an electrolyte membrane containing the fluorinated polymer (I), the platinum-containing material, cerium and the woven fabric.
[0180] Specific examples of the water-soluble cerium salt include cerium acetate, cerium chloride, cerium nitrate, cerium sulfate, and cerium carbonate.
[0181] In addition, instead of the dispersion liquid in which the platinum-containing substance is dispersed, a solution containing platinum ions may be used to precipitate the platinum ions in the film.
[0182] As another example of the method for producing the electrolyte membrane, the following method can be mentioned.
[0183] First, a composition comprising a fluorinated polymer (I), a platinum-containing substance, and a water-soluble cerium salt is used to obtain a film P1 comprising a fluorinated polymer (I), a platinum-containing substance, and cerium.
[0184] Next, the membrane P1, the woven fabric, and the membrane P1 are arranged in this order and laminated using a laminating roll or a vacuum laminating device to obtain an electrolyte membrane comprising the fluorinated polymer (I), the platinum-containing material, cerium, and the woven fabric.
[0185] By these methods, a single-layer electrolyte membrane (corresponding to the above-mentioned first electrolyte layer) is obtained.
[0186] As an example of a method for manufacturing an electrolyte membrane as a multilayer structure, the following method can be cited: a first electrolyte layer comprising a fluorinated polymer (I), a platinum-containing substance, and cerium and an electrolyte layer (equivalent to the above-mentioned second electrolyte layer) which does not contain platinum-containing substances and cerium or has a lower concentration of platinum-containing substances and cerium than the first electrolyte layer are stacked and then hot pressed. It should be noted that the woven fabric only needs to be contained in at least one of the first electrolyte layer and the second electrolyte layer. Thus, a multilayer electrolyte membrane is obtained. For the multilayer electrolyte membrane thus obtained, the platinum-containing substances and cerium are biased toward one surface of the electrolyte membrane.
[0187] As another example of a method for manufacturing an electrolyte membrane as a multilayer structure, the following method can be cited: on a second electrolyte layer comprising a woven cloth, a dispersion containing a fluorine-containing polymer (I) and a platinum-containing substance is coated and dried, and then, after immersing in a solution containing a water-soluble cerium salt, the dispersion is dried to form a first electrolyte layer on the second electrolyte layer.
[0188] As the fluorinated polymer (I'), a polymer of a fluorinated monomer (hereinafter also referred to as "fluorinated monomer (S')") having a group that can be converted into a sulfonic acid type functional group (hereinafter also referred to as "fluorinated polymer (S')") is preferred, and a copolymer of a fluorinated olefin and a monomer having a group that can be converted into a sulfonic acid type functional group and a fluorine atom is particularly preferred.
[0189] The fluorinated polymer (S') will be described in detail below.
[0190] As the method for copolymerizing the fluorinated polymer (S'), known methods such as solution polymerization, suspension polymerization and emulsion polymerization can be employed.
[0191] As the fluorinated olefin, there can be mentioned those exemplified above, and TFE is preferred from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtained fluorinated polymer (S).
[0192] The fluorinated olefins may be used alone or in combination of two or more.
[0193] Examples of the fluorine-containing monomer (S′) include compounds having one or more fluorine atoms in the molecule, having an ethylenic double bond, and having a group that can be converted into a sulfonic acid type functional group.
[0194] As the fluorinated monomer (S'), a compound represented by the formula (2) is preferred from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtained fluorinated polymer (S).
[0195] Formula (2) CF2=CF-L-(A) n
[0196] In formula (2), L and n are as defined above.
[0197] A is a group that can be converted into a sulfonic acid type functional group. The group that can be converted into a sulfonic acid type functional group is preferably a functional group that can be converted into a sulfonic acid type functional group by hydrolysis. As specific examples of the group that can be converted into a sulfonic acid type functional group, -SO2F, -SO2Cl, -SO2Br can be cited. When A is multiple, the multiple A can be the same or different.
[0198] As the compound represented by formula (2), the compound represented by formula (2-1), the compound represented by formula (2-2), the compound represented by formula (2-3), and the compound represented by formula (2-4) are preferred.
[0199] Formula (2-1) CF2=CF-OR f1 -A
[0200] Formula (2-2) CF2=CF-R f1 -A
[0201] Formula (2-3)
[0202] R in the formula f1 , R f2 , r and A are defined as above.
[0203] Formula (2-4)
[0204] R in the formula f1 , R f2 , R f3 , r, m and A are defined as above.
[0205] As the compound represented by the formula (2-1) and the compound represented by the formula (2-1), the compound represented by the formula (2-5) is preferred.
[0206] Formula (2-5) CF2 = CF-(CF2) x -(OCF2CFY) y -O-(CF2) z -SO3F
[0207] The definitions of x, y, z and Y in the formula are the same as those of the compound represented by the above formula (1-5).
[0208] Specific examples of the compound represented by formula (2-1) include the following compounds: wherein w is an integer of 1 to 8, and x is an integer of 1 to 5.
[0209] CF2=CF-O-(CF2) w -SO2F
[0210] CF2=CF-O-CF2CF(CF3)-O-(CF2) w -SO2F
[0211] CF2=CF-[O-CF2CF(CF3)] x -SO2F
[0212] Specific examples of the compound represented by formula (2-2) include the following compounds: wherein w in the formula is an integer of 1 to 8.
[0213] CF2=CF-(CF2) w -SO2F
[0214] CF2=CF-CF2-O-(CF2) w -SO2F
[0215] As the compound represented by the formula (2-3), the compound represented by the formula (2-3-1) is preferred.
[0216] Formula (2-3-1)
[0217] R in the formula f4 , R f5 , r and A are defined as above.
[0218] Specific examples of the compound represented by formula (2-3-1) include the following.
[0219]
[0220] As the compound represented by the formula (2-4), the compound represented by the formula (2-4-1) is preferred.
[0221] Formula (2-4-1)
[0222] R in the formula f1 , R f2 and A are defined as above.
[0223] Specific examples of the compound represented by formula (2-4-1) include the following.
[0224]
[0225] The fluorinated monomer (S') may be used alone or in combination of two or more.
[0226] In the production of the fluorinated polymer (S'), other monomers may be used in addition to the fluorinated olefin and the fluorinated monomer (S'). Examples of the other monomers include those exemplified above.
[0227] The ion exchange capacity of the fluorinated polymer (I') can be adjusted by changing the content of the group capable of being converted into an ion exchange group in the fluorinated polymer (I').
[0228] Specific examples of the method for converting the groups in the precursor film that can be converted into ion exchange groups into ion exchange groups include a method of subjecting the precursor film to a treatment such as a hydrolysis treatment or an acidification treatment.
[0229] Among them, a method of bringing the precursor film into contact with an alkaline aqueous solution is preferred.
[0230] Specific examples of the method of bringing the precursor film into contact with the alkaline aqueous solution include a method of immersing the precursor film in the alkaline aqueous solution and a method of spraying and applying the alkaline aqueous solution to the surface of the precursor film.
[0231] The temperature of the alkaline aqueous solution is preferably 30° C. or higher, more preferably 40° C. or higher, and preferably 100° C. or lower. The contact time between the precursor film and the alkaline aqueous solution is preferably 3 minutes or higher, more preferably 5 minutes or higher, and preferably 150 minutes or lower, more preferably 50 minutes or lower.
[0232] The alkaline aqueous solution preferably contains an alkali metal hydroxide, a water-soluble organic solvent and water.
[0233] Examples of the alkali metal hydroxide include sodium hydroxide and potassium hydroxide.
[0234] In this specification, a water-soluble organic solvent refers to an organic solvent that is easily soluble in water, and specifically, an organic solvent having a solubility of 0.1 g or more in 1000 ml (20° C.) of water is preferred, and an organic solvent having a solubility of 0.5 g or more is particularly preferred. The water-soluble organic solvent preferably includes at least one selected from the group consisting of aprotic organic solvents, alcohols, and amino alcohols, and particularly preferably includes an aprotic organic solvent.
[0235] The water-soluble organic solvent may be used alone or in combination of two or more.
[0236] Specific examples of the aprotic organic solvent include dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone, and dimethyl sulfoxide is preferred.
[0237] Specific examples of the alcohols include methanol, ethanol, isopropanol, butanol, methoxyethoxyethanol, butoxyethanol, butyl carbitol, hexyloxyethanol, octanol, 1-methoxy-2-propanol, and ethylene glycol.
[0238] Specific examples of amino alcohols include ethanolamine, N-methylethanolamine, N-ethylethanolamine, 1-amino-2-propanol, 1-amino-3-propanol, 2-aminoethoxyethanol, 2-aminothioethoxyethanol, and 2-amino-2-methyl-1-propanol.
[0239] The concentration of the alkali metal hydroxide is preferably 1% by mass or more, more preferably 3% by mass, and is preferably 60% by mass or less, more preferably 55% by mass or less in the alkaline aqueous solution.
[0240] The content of the water-soluble organic solvent is preferably 1% by mass or more, more preferably 3% by mass or more, and is preferably 60% by mass or less, more preferably 55% by mass or less in the alkaline aqueous solution.
[0241] The concentration of water is preferably 39 to 80% by mass in the alkaline aqueous solution.
[0242] After the precursor film is brought into contact with the alkaline aqueous solution, a treatment for removing the alkaline aqueous solution may be performed. As a method for removing the alkaline aqueous solution, for example, a method of washing the precursor film brought into contact with the alkaline aqueous solution with water is exemplified.
[0243] After the precursor film is brought into contact with the alkaline aqueous solution, the resulting film may be brought into contact with an acidic aqueous solution to convert the ion exchange groups into an acidic form.
[0244] Specific examples of the method of bringing the precursor film into contact with the acidic aqueous solution include a method of immersing the precursor film in the acidic aqueous solution and a method of spraying and applying the acidic aqueous solution to the surface of the precursor film.
[0245] The acidic aqueous solution preferably contains an acid component and water.
[0246] Specific examples of the acid component include hydrochloric acid and sulfuric acid.
[0247] [Membrane Electrode Assembly]
[0248] The membrane electrode assembly of the present invention includes the electrolyte membrane, a cathode catalyst layer disposed on one surface of the electrolyte membrane, and an anode catalyst layer disposed on the other surface of the electrolyte membrane.
[0249] Figure 2 This is a cross-sectional view schematically showing an example of the membrane electrode assembly of the present invention, and is a view showing a case where the electrolyte membrane has a single-layer structure. Figure 2 In the example, the membrane electrode assembly 20 includes: an anode 22 having a catalyst layer 26 and a gas diffusion layer 28, a cathode 24 having a catalyst layer 26 and a gas diffusion layer 28, and an electrolyte membrane 10 arranged between the anode 22 and the cathode 24 in contact with the catalyst layer 26.
[0250] exist Figure 2 In the example of FIG. 1 , the electrolyte membrane has a single-layer structure, but the electrolyte membrane may have a multi-layer structure. Specific examples and preferred embodiments of the electrolyte membrane having a multi-layer structure are as described above.
[0251] Figure 3 This is a cross-sectional view schematically showing an example of the membrane electrode assembly of the present invention, and is a view showing a case where the electrolyte membrane has a multilayer structure. Figure 3 The structure of the membrane electrode assembly 120 includes an electrolyte membrane 100 instead of Figure 2 In addition to the electrolyte membrane 10, Figure 2 The structure of the membrane electrode assembly 20 is the same. Figure 3 The electrolyte membrane 100 includes a first electrolyte layer 100A and a second electrolyte layer 100B arranged in this order from the anode 22 side to the cathode 24 side.
[0252] The first electrolyte layer 100A contains a fluorinated polymer (I), a platinum-containing material, and cerium.
[0253] The second electrolyte layer 100B contains the fluorinated polymer (I). The second electrolyte layer 100B has a lower concentration of platinum-containing substances and cerium than the first electrolyte layer, or contains no platinum-containing substances and cerium.
[0254] The woven fabric is included in at least one of the first electrolyte layer 100A and the second electrolyte layer 100B.
[0255] exist Figure 3 In the example shown, the electrolyte membrane has a two-layer structure, but the electrolyte membrane may have a structure of three or more layers.
[0256] <Anode and cathode>
[0257] The anode and cathode each have a catalyst layer. Figure 2 and Figure 3 In the example of FIG. 2 , the anode 22 and the cathode 24 each have a catalyst layer 26 and a gas diffusion layer 28 .
[0258] Specific examples of the catalyst layer include a layer containing a catalyst and a polymer having an ion exchange group.
[0259] Specific examples of the catalyst include: a supported catalyst containing platinum, a platinum alloy or a platinum catalyst having a core-shell structure supported on a carbon carrier, an iridium oxide catalyst, a composite oxide catalyst containing iridium and other metal elements, an alloy containing iridium oxide, and a catalyst containing iridium oxide having a core-shell structure. As a carbon carrier, carbon black powder can be mentioned.
[0260] Examples of the polymer having an ion exchange group include fluorinated polymers having an ion exchange group, and for example, the above-mentioned fluorinated polymer (I) is used.
[0261] Average 1cm 2 The mass of the catalyst metal in the catalyst layer is preferably 0.05 mg / cm 2 More preferably, more than 0.05 mg / cm 2 , more preferably 0.2 mg / cm 2 Above, preferably 4 mg / cm 2 Below, more preferably 2 mg / cm 2 Below, more preferably 1 mg / cm 2 the following.
[0262] The mass ratio of the catalyst to the polymer having ion exchange groups in the catalyst layer (mass of the catalyst / mass of the polymer having ion exchange groups) is preferably 2-6.
[0263] The catalyst layer preferably contains a thickener from the viewpoint of improving the dispersibility of the catalyst and suppressing aggregation.
[0264] Specific examples of thickeners include urethane thickeners, polyacrylic acid thickeners, polyamide thickeners, cellulose thickeners, clay minerals such as bentonite, etc. In addition, ZEOROLA (registered trademark) H (manufactured by ZEON Corporation of Japan) and the like can also be used as a thickener.
[0265] When the catalyst layer contains a thickener, the content of the thickener is preferably 2 mass % or more, more preferably 3 mass % or more, and preferably 7 mass % or less, more preferably 6 mass % or less, based on the total mass of the catalyst layer-forming coating liquid described below.
[0266] The gas diffusion layer has the function of rapidly diffusing the gas generated by the catalyst layer to the outside of the catalyst layer and the function of being a current collector. Specific examples of the gas diffusion layer include carbon paper, carbon cloth, carbon felt, titanium oxide fiber sintered body, and titanium oxide particle sintered body. The anode side is at a high potential, and if a carbon material is used, it will be oxidized, so it is preferred to use a titanium oxide fiber sintered body or a titanium oxide particle sintered body. The titanium oxide sintered body can be plated with platinum or the like as needed.
[0267] The cathode gas diffusion layer may be subjected to water-repellent treatment using PTFE or the like.
[0268] Figure 2 and Figure 3 The membrane electrode assembly includes the gas diffusion layer 28, but the gas diffusion layer is an optional component and the membrane electrode assembly does not necessarily need to include the gas diffusion layer.
[0269] From the viewpoint of further improving the effects of the present invention, the thickness of the anode and cathode is each independently preferably 5 μm or more, and preferably 100 μm or less, more preferably 50 μm or less, further preferably 30 μm or less, and particularly preferably 15 μm or less.
[0270] The film thickness of the anode and the cathode was measured using an image obtained by measuring a cross section cut in the film thickness direction of the membrane electrode assembly using a laser microscope, and the arithmetic mean value was calculated at any 20 locations.
[0271] <Method for Manufacturing Membrane Electrode Assembly>
[0272] The method for producing the membrane electrode assembly is a method of forming the cathode catalyst layer on one surface side of an electrolyte membrane and forming the anode catalyst layer on the other surface side of the electrolyte membrane.
[0273] As an example of a method for manufacturing a membrane electrode assembly, the following method can be cited: using a stack having an anode catalyst layer and a release substrate (e.g., an ETFE sheet), and a stack having a cathode catalyst layer and a release substrate (e.g., an ETFE sheet), the catalyst layers are bonded to both sides of the electrolyte membrane, and then the release substrate is peeled off.
[0274] The laminate may include a gas diffusion layer between the catalyst layer and the releasable substrate. In this case, the gas diffusion layer may be formed on the surface of the catalyst layer opposite to the electrolyte membrane.
[0275] It should be noted that the method for producing the catalyst layer includes applying a coating liquid for forming the catalyst layer to a predetermined position (e.g., the surface of a release substrate) and drying it as required. The coating liquid for forming the catalyst layer is a liquid in which a polymer having an ion exchange group and a catalyst are dispersed in a dispersion medium.
[0276] <Purpose>
[0277] The membrane electrode assembly of the present invention is suitable for use in a solid polymer water electrolysis device.
[0278] [Water electrolysis device]
[0279] The water electrolysis device of the present invention comprises: the membrane electrode assembly described above; a water supply unit that supplies water to the anode catalyst layer side; and a power supply unit that is electrically connected to the anode catalyst layer side and the cathode catalyst layer side.
[0280] In the water electrolysis device of the present invention, when a DC voltage is applied by the power supply unit while water is supplied to the anode catalyst layer side by the water supply unit, water is decomposed on the anode catalyst layer side to generate oxygen and protons. In addition, on the cathode catalyst layer side, the protons that move to the cathode catalyst layer side via the electrolyte membrane obtain electrons to generate hydrogen.
[0281] The water electrolysis device of the present invention may have the same configuration as a known water electrolysis device (for example, an oxygen recovery member for recovering generated oxygen gas, a hydrogen recovery member for recovering generated hydrogen gas) except for the above-mentioned members.
[0282] Example
[0283] Hereinafter, the present invention will be described in detail with reference to examples. Examples 1 to 5 are embodiments, and Examples 6 to 7 are comparative examples. However, the present invention is not limited to these examples.
[0284] [Ion exchange capacity of fluorinated polymer]
[0285] The fluoropolymer was placed in a glove box with dry nitrogen for 24 hours, and the dry mass of the fluoropolymer was measured. Thereafter, the fluoropolymer was immersed in a 2 mol / L sodium chloride aqueous solution at 60°C for 1 hour. The fluoropolymer was washed with ultrapure water, taken out, and the liquid immersed in the fluoropolymer was titrated with a 0.1 mol / L sodium hydroxide aqueous solution to obtain the ion exchange capacity (milliequivalent / g dry resin) of the fluoropolymer.
[0286] In addition, in the table|surface mentioned later, IEC (meq / g) means ion exchange capacity (milliequivalent / g dry resin).
[0287] [Average particle size of platinum-containing material (D50)]
[0288] After the platinum-containing material / fluorinated polymer dispersion is dispersed (dispersion treatment based on a bead mill), the particle size distribution is measured by a laser diffraction particle size distribution measuring device (MicrotracBEL Corp., MT3300EXII-SDC) to obtain the volume-based cumulative 50% particle size of the platinum-containing material. The arithmetic mean of the cumulative 50% particle size at the three points obtained is used as D50.
[0289] [Thickness of electrolyte layer]
[0290] The thickness of each electrolyte layer was measured at 23° C. and 50% RH using an enlarged image (objective magnification: 50 times) of a cross section of the electrolyte layer taken with a laser microscope (product name “VK-X1000”, manufactured by KEYENCE CORPORATION).
[0291] [Amount of substance of ion exchange groups in fluorinated polymer]
[0292] The amount (mol) of the ion exchange group contained in the fluorinated polymer is calculated by obtaining the milliequivalent weight of the ion exchange group from the following formula and dividing the obtained milliequivalent weight of the ion exchange group by the ion valence of the ion exchange group. For example, when the ion exchange group is a sulfonic acid group, the ion valence is 1.
[0293] Milliequivalent weight of ion exchange groups = dry mass of fluoropolymer (g) × ion exchange capacity (miequivalent weight / g dry resin)
[0294] Here, the dry mass (g) of the fluorinated polymer is determined as follows: The electrolyte membrane is cut into 7 cm×7 cm pieces, dried for 72 hours in a glove box blowing dry nitrogen, and then the mass is measured in the glove box.
[0295] [Amount of cerium]
[0296] The method for measuring the amount of cerium substance in the electrolyte membrane is as follows.
[0297] The film cut into a size of 4 cm×4 cm was immersed in 10 mL of hydrochloric acid at 80° C. for 3 hours to extract cerium ions in the film. The film was taken out and the cerium ion concentration in the hydrochloric acid was analyzed by ICP emission spectrometry to determine the amount (mol) of cerium contained in the film.
[0298] [Concentration of hydrogen in oxygen]
[0299] The membrane electrode assembly was sandwiched between platinum-coated titanium fiber sintered bodies (produced by Bekaert) with a thickness of 0.25 mm and a porosity of 60%, and the membrane electrode assembly was installed in an electrode area of 16 cm using a platinum-coated titanium plate with a linear flow path as a spacer. 2 When clamping the membrane electrode assembly, a pressure of 1.5 MPa is applied to the electrode portion to tighten it.
[0300] Next, in order to make the electrolyte membrane and the two electrode ionomers fully hydrated, pure water with a conductivity of 1.0 μS / cm or less, a temperature of 60°C, and normal pressure was supplied to the anode side and the cathode side at a flow rate of 50 mL / min for 8 hours. Thereafter, pure water with a conductivity of 1.0 μS / cm or less and a temperature of 60°C was supplied to the anode side at a flow rate of 50 mL / min, and the back pressure was set to normal pressure at both the anode and the cathode, and was maintained at 16 A (current density 1 A / cm 2 ), and water electrolysis was performed for 4 hours as a warm-up exercise. Then, as a formal measurement, the current density was 0 to 32A (0 to 2A / cm 2 ) range causes the current to increase step by step by 2 A each time.
[0301] Thereafter, pure water with a conductivity of 1.0 μS / cm or less, a temperature of 60°C, and normal pressure was supplied to the battery at 50 mL / min, and the back pressure was set to normal pressure at both the anode and cathode, and the current was maintained at 3.2 A (current density 0.2 A / cm) using a high current constant potential / constant current meter HCP-803 (manufactured by BioLogic). 2 ) for 12 hours. After 12 hours, water was separated from the gas discharged from the anode side, and the hydrogen concentration in the gas was measured by micro GC (Agilent 490, manufactured by Agilent), and the hydrogen concentration in oxygen (H2 concentration in O2) was evaluated according to the following criteria. It can be said that the smaller the value of H2 concentration in O2, the better the low gas permeability of the electrolyte membrane.
[0302] ◎: less than 0.05% by volume
[0303] ○: 0.05 volume % or more and less than 0.10 volume %
[0304] ×: 0.10 volume % or more
[0305] [Fluoride release rate]
[0306] The membrane electrode assembly was sandwiched between platinum-coated titanium fiber sintered bodies (produced by Bekaert) with a thickness of 0.25 mm and a porosity of 60%, and the membrane electrode assembly was installed in an electrode area of 16 cm using a platinum-coated titanium plate with a linear flow path as a spacer. 2 The membrane electrode assembly was clamped and fastened in such a way that a pressure of 1.5 MPa was applied to the electrode portion.
[0307] Next, in order to make the electrolyte membrane and the two electrode ionomers fully hydrated, pure water with a conductivity of 1.0 μS / cm or less, a temperature of 60°C, and normal pressure was supplied to the anode catalyst layer side and the cathode catalyst layer side at a flow rate of 50 mL / min for 8 hours. Thereafter, pure water with a conductivity of 1.0 μS / cm or less and a temperature of 60°C was supplied to the anode catalyst layer side at a flow rate of 50 mL / min, and the back pressure was set to normal pressure in both the anode catalyst layer and the cathode catalyst layer, and was maintained at 16 A (current density 1 A / cm 2 ), and water electrolysis was performed for 4 hours as a warm-up exercise. Thereafter, the water supply to the anode catalyst layer was changed to 150 mL / min, the back pressure was changed to 50 kPa for both the anode and cathode, and the current density was continued for 1000 hours at 1 A / cm 2 The following operation.
[0308] Wastewater discharged from the cathode catalyst layer side was sampled between 500 and 1000 hours after warm-up. The amount of fluoride ions contained in the wastewater was quantified and averaged by ion chromatography, and the average amount of fluoride ions per unit electrode area per unit time was calculated as the fluorine release rate, which was evaluated according to the following criteria. It can be said that the smaller the value of the fluorine release rate, the more the decomposition of the fluorine-containing polymer is suppressed, and the better the chemical durability of the electrolyte membrane.
[0309] ◎: Less than 1.0×10 -6 mg / (h·cm 2 )
[0310] ○:1.0×10 -6 mg / (h·cm 2 ) and less than 3.0×10 -6 mg / (h·cm 2 )
[0311] ×: 3.0×10 -6 mg / (h·cm 2 )above
[0312] [Presence of wrinkles]
[0313] The wrinkle formation state of the electrolyte membrane after immersion in water was visually confirmed. The temperature of the immersion water was set to 100° C. and the immersion time was set to 24 hours. The evaluation criteria were as follows.
[0314] ◎: No wrinkles were observed at all
[0315] ○: Slightly wrinkled
[0316] ×: Many wrinkles were observed
[0317] [Operability]
[0318] During the production of the membrane electrode assembly described below, the workability was evaluated based on the time from setting the stack (anode catalyst layer decal / electrolyte membrane / cathode catalyst layer decal) on the flat press until it reached a state ready for hot pressing. The evaluation criteria were as follows.
[0319] Here, the smaller the warpage of the laminate is, the shorter the time from setting to the start of hot pressing is, and the better the handleability is.
[0320] In addition, in the table mentioned later, "-" in the evaluation result column of operability means that the evaluation of operability was not carried out.
[0321] ○: The time from setting the laminate on the flat press to the time when hot pressing can be started is within 5 minutes
[0322] ×: The time from setting the laminate on the flat plate press to reaching a state ready for hot pressing to exceed 5 minutes
[0323] [Electrolyte layer X1]
[0324] <Production of fluorinated polymer (I'-1)>
[0325] CF2=CF2 was copolymerized with a monomer (X) represented by the following formula (X) to obtain a fluorinated polymer (I'-1) (ion exchange capacity: 1.25 meq / g dry resin).
[0326] CF2=CF-O-CF2CF(CF3)-O-CF2CF2-SO2F···(X)
[0327] The ion exchange capacity described in the above [Production of Fluoropolymer (I'-1)] means the ion exchange capacity of the fluorinated polymer obtained when the fluorinated polymer (I'-1) is hydrolyzed by the step described later.
[0328] <Manufacturing of Thin Film-Attached Substrate Y1>
[0329] A fluorinated polymer (I'-1) is attached to a substrate formed of a linear low-density polyethylene (LLDPE) film (melting point: 110-120°C) by melt extrusion to obtain a film-attached substrate Y1 having a film α1 (thickness 45 μm) formed of the fluorinated polymer (I'-1) formed on the substrate.
[0330] <Manufacture of woven fabrics>
[0331] The warp and weft yarns were made of 18.6 denier yarns made of PFA, and the PFA yarns were plain woven so that the density was 100 yarns / inch to obtain woven fabric A1. The weight per unit area of woven fabric A1 was 16.3 g / m 2 .
[0332] <Manufacturing of Electrolyte Layer X1>
[0333] The substrate with film Y1 / woven fabric A1 / substrate with film Y1 are stacked in this order. The substrate with film Y1 is arranged so that the film α1 in the substrate with film Y1 is in contact with the woven fabric A1.
[0334] The stacked components were heated to 160°C and subjected to a surface pressure of 30 MPa / m. 2 After heat-compression bonding for 10 minutes using a flat plate press, the substrates on both sides were peeled off at a temperature of 50° C. to obtain a precursor film.
[0335] The precursor film was immersed in a solution of dimethyl sulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95° C. for 30 minutes, and the groups in the precursor film that can be converted into sulfonic acid-type functional groups were hydrolyzed and converted into K-type sulfonic acid-type functional groups, and then washed with water. Thereafter, the obtained film was immersed in 1M sulfuric acid, and the terminal groups were converted from K-type to H-type, and then dried to obtain an electrolyte layer X1 (thickness 90 μm).
[0336] [Electrolyte layer X2]
[0337] <Preparation of Platinum / Electrolyte Polymer Dispersion>
[0338] A fluorinated polymer (ion exchange capacity: 1.25 milliequivalents / gram of dry resin) obtained by copolymerizing CF2=CF2 and the above-mentioned monomer (X) and hydrolyzing and acid-treating to obtain an acidic form was dispersed in a solvent of water / ethanol=40 / 60 (mass %) at a solid content concentration of 20.0% to obtain a dispersion. Cerium carbonate hydrate (Ce2(CO3)3·8H2O, 0.3 g) was added to the dispersion (200 g) and stirred at 50°C for 24 hours. After the stirring started, bubbles caused by the generation of CO2 were confirmed to obtain a uniform and transparent dispersion (hereinafter also referred to as "dispersion D-1"). Ethanol (4.00 g) and water (6.70 g) were added to the obtained dispersion D-1 (1.75 g), and a platinum-supported carbon catalyst ("TEC10E50E" manufactured by Tanaka Precious Metals Co., Ltd., a catalyst in which platinum as a platinum-containing substance is supported on a carbon carrier) (1.30 g) containing 45.6% by mass of platinum was further added to the dispersion. 150 g of beads having a diameter of 5 mm were further added to the obtained mixture, and after being treated with a planetary bead mill (rotation speed of 300 rpm) for 30 minutes, water (4.87 g) and dispersion D-1 (113.65 g) were added, and then treated with a planetary bead mill (rotation speed of 200 rpm) for 60 minutes to obtain a platinum-containing substance / fluorine-containing polymer dispersion D-2 having a solid content concentration of 18.4% by mass.
[0339] <Manufacturing of Electrolyte Layer X2>
[0340] Dispersion D-2 was applied to an ETFE sheet using an applicator to a thickness of 10 μm after drying, dried at 80°C for 10 minutes, and then heat treated at 150°C for 30 minutes to obtain an electrolyte layer X2 (thickness 10 μm) containing a fluorine-containing polymer, a platinum-containing material, and cerium.
[0341] [Electrolyte layer X3]
[0342] The above-mentioned dispersion D-2 is applied to an ETFE sheet using an applicator in a manner such that the thickness after drying becomes 45 μm, and then dried at 80°C for 10 minutes, and then heat treated at 150°C for 30 minutes to obtain a thin film substrate Y2 having a thin film α2 (thickness 45 μm) containing a fluorine-containing polymer, a platinum-containing substance and cerium formed on the substrate.
[0343] The substrate with film Y2 / woven fabric A1 / substrate with film Y2 were stacked in this order. The substrate with film Y2 was arranged so that the film α2 in the substrate with film Y2 was in contact with the woven fabric A1.
[0344] The stacked components were heated to 160°C and subjected to a surface pressure of 30 MPa / m. 2 After heat-compression bonding for 10 minutes using a flat plate press, the substrates on both sides were peeled off at a temperature of 50° C. to obtain an electrolyte layer X3 (thickness 90 μm).
[0345] [Electrolyte layer X4]
[0346] An electrolyte layer X4 (thickness 10 μm) was obtained in the same manner as electrolyte X2 except that the amount of cerium carbonate hydrate added was changed to 0.8 g.
[0347] [Electrolyte layer X5]
[0348] The above-mentioned fluorinated polymer (I'-1) is attached to a substrate formed by a linear low-density polyethylene (LLDPE) film (melting point: 110-120°C) by melt extrusion to obtain a film-attached substrate Y3 having a film α3 (thickness 30 μm) formed on the substrate and formed with the fluorinated polymer (I'-1).
[0349] The substrate with film Y3 / woven fabric A1 / substrate with film Y3 are stacked in this order. The substrate with film Y3 is arranged so that the film α3 in the substrate with film Y3 is in contact with the woven fabric A1.
[0350] The stacked components were heated to 160°C and subjected to a surface pressure of 30 MPa / m. 2 After heat-compression bonding for 10 minutes using a flat plate press, the substrates on both sides were peeled off at a temperature of 50° C. to obtain a precursor film.
[0351] The precursor film was immersed in a solution of dimethyl sulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95°C for 30 minutes, and the groups in the precursor film that can be converted into sulfonic acid type functional groups were hydrolyzed and converted into K-type sulfonic acid type functional groups, and then washed with water. Thereafter, the obtained film was immersed in 1M sulfuric acid, and the terminal groups were converted from K-type to H-type, and then dried to obtain an electrolyte layer X5 (thickness 60 μm).
[0352] [Electrolyte layer X6]
[0353] A fluorinated polymer (ion exchange capacity: 1.25 milliequivalents / gram of dry resin) obtained by copolymerizing CF2=CF2 and the above-mentioned monomer (X) and undergoing hydrolysis and acid treatment to become an acidic type is dispersed in a solvent of water / ethanol = 40 / 60 (mass %) at a solid content concentration of 20.0% to obtain a dispersion D-6.
[0354] The dispersion D-6 was applied to the ETFE sheet using an applicator to a thickness of 10 μm after drying, dried at 80°C for 10 minutes, and heat treated at 150°C for 30 minutes to obtain an electrolyte layer X6 (thickness 10 μm) containing a fluorinated polymer.
[0355] [Electrolyte layer X7]
[0356] An electrolyte layer X7 (thickness 10 μm) was obtained in the same manner as electrolyte X2 except that the amount of cerium carbonate hydrate added was changed to 2.5 g.
[0357] [Example 1]
[0358] The electrolyte layer X1 and the electrolyte layer X2 were stacked and pressed using a flat plate press at 150° C. and a surface pressure of 30 MPa / m 2 After hot pressing for 10 minutes under the conditions of , the film was cooled to room temperature to obtain the electrolyte membrane 1 (thickness 100 μm) of Example 1.
[0359] The ratio (mol%) of the amount of cerium to the amount of ion exchange groups of the electrolyte membrane 1 was calculated based on the amount of ion exchange groups (sulfonic acid groups) and the amount of cerium obtained by the above method and is shown in Table 1. It should be noted that in the table, the ratio of the amount of cerium to the amount of ion exchange groups is abbreviated as "Ce / IEG (mol%)".
[0360] A polymer obtained by copolymerizing CF2=CF2 and the above-mentioned monomer (X) and undergoing hydrolysis and acid treatment to become an acid-type polymer (ion exchange capacity: 1.10 milliequivalents / g of dry resin) is dispersed in a solvent of water / ethanol = 40 / 60 (mass %) at a solid content concentration of 26.0% to obtain a dispersion (hereinafter also referred to as "dispersion Y").
[0361] Ethanol (18.06 g) and ZEOROLA (registered trademark) H (manufactured by ZEON Corporation of Japan, thickener) (10.58 g) were added to the dispersion Y (33.0 g), and mixed at 2200 rpm for 5 minutes using a rotation and revolution mixer (manufactured by Thinky, Co., Ltd., Awatori Rentaro). Ethanol (46.44 g) and water (75.75 g) were added to the mixed composition (54.06 g), and a specific surface area of 100 m2 containing 74.8% by mass of iridium was further added. 2 / g of iridium oxide catalyst (produced by Tanaka Kikinzoku Co., Ltd.) (40.0 g) was added. The obtained mixture was treated with a planetary bead mill (rotation speed: 300 rpm) for 90 minutes to obtain an anode catalyst ink having a solid content concentration of 22% by mass.
[0362] On the ETFE sheet, iridium was applied with an applicator to a thickness of 1.0 mg / cm 2 The anode catalyst ink was applied in a manner of , dried at 80° C. for 10 minutes, and then heat treated at 150° C. for 15 minutes to obtain an anode catalyst layer decal.
[0363] Water (59.4 g) and ethanol (39.6 g) were added to a supported catalyst (“TEC10E50E” manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) (11 g) in which 46% by mass of platinum was supported on carbon powder, and mixed and pulverized using an ultrasonic homogenizer to obtain a catalyst dispersion.
[0364] Dispersion Y (20.1 g), ethanol (11 g) and ZEOROLA (registered trademark) H (manufactured by ZEON Corporation, Japan, thickener) (6.3 g) were pre-mixed and kneaded into a mixed solution (29.2 g) in the catalyst dispersion. Water (3.66 g) and ethanol (7.63 g) were added to the obtained dispersion, and mixed for 60 minutes using a paint conditioner to adjust the solid content concentration to 10.0% by mass to obtain a cathode catalyst ink.
[0365] The cathode catalyst ink was applied to an ETFE sheet using a die coater, dried at 80°C, and then heat treated at 150°C for 15 minutes to obtain a platinum content of 0.4 mg / cm 2 The cathode catalyst layer decal.
[0366] The surface of the electrolyte membrane 1 on the electrolyte layer X2 side is opposite to the surface of the anode catalyst layer decal on which the catalyst layer exists, and the surface of the electrolyte membrane 1 on the electrolyte layer X1 side is opposite to the surface of the cathode catalyst layer decal on which the catalyst layer exists, and heating pressing is performed at a pressing temperature of 150°C for 10 minutes and a pressure of 3MPa to join the anode catalyst layer, the electrolyte membrane 1 and the cathode catalyst layer, and the temperature is lowered to 70°C and then the pressure is released and taken out, and the ETFE sheets of the anode catalyst layer decal and the cathode catalyst layer decal are peeled off to obtain an electrode with an area of 16cm 2 The obtained membrane electrode assembly was subjected to the above-mentioned evaluations. The results are shown in Table 1.
[0367] [Example 2]
[0368] The electrolyte layer X3 was used as the electrolyte membrane 2 (thickness 90 μm) of Example 2. Table 1 shows the ratio (mol %) of the amount of cerium substance to the amount of ion exchange group substance.
[0369] The membrane electrode assembly of Example 2 was obtained in the same manner as Example 1 except that electrolyte membrane 2 was used instead of electrolyte membrane 1. The anode catalyst layer decal was bonded to one side of electrolyte membrane 2, and the cathode catalyst layer decal was bonded to the other side of electrolyte membrane 2.
[0370] The membrane electrode assembly of Example 2 was subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0371] [Example 3]
[0372] The electrolyte layer X1 and the electrolyte layer X4 were stacked and pressed at 150°C and a surface pressure of 30 MPa / m using a flat plate press. 2 After hot pressing for 10 minutes under the conditions of , the film was cooled to room temperature to obtain an electrolyte membrane 3 (thickness 100 μm) of Example 3. Table 1 shows the ratio (mol %) of the amount of cerium to the amount of ion exchange groups.
[0373] The membrane electrode assembly of Example 3 was obtained in the same manner as Example 1 except that the electrolyte membrane 3 was used instead of the electrolyte membrane 1. It should be noted that the anode catalyst layer decal was bonded to the surface of the electrolyte membrane 3 on the electrolyte layer X4 side, and the cathode catalyst layer decal was bonded to the surface of the electrolyte membrane 3 on the electrolyte layer X1 side.
[0374] The membrane electrode assembly of Example 3 was subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0375] [Example 4]
[0376] The electrolyte layer X5 and the electrolyte layer X4 were stacked and pressed at 150°C and a surface pressure of 30 MPa / m using a flat plate press. 2After hot pressing for 10 minutes under the conditions of , the film was cooled to room temperature to obtain an electrolyte membrane 4 (70 μm thick) of Example 4. Table 1 shows the ratio (mol %) of the amount of cerium to the amount of ion exchange groups.
[0377] The membrane electrode assembly of Example 4 was obtained in the same manner as in Example 1 except that the electrolyte membrane 4 was used instead of the electrolyte membrane 1. It should be noted that the anode catalyst layer decal was bonded to the surface of the electrolyte membrane 4 on the electrolyte layer X4 side, and the cathode catalyst layer decal was bonded to the surface of the electrolyte membrane 4 on the electrolyte layer X5 side.
[0378] The membrane electrode assembly of Example 4 was subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0379] [Example 5]
[0380] The electrolyte layer X1 and the electrolyte layer X7 were stacked and pressed at 150°C and a surface pressure of 30 MPa / m using a flat plate press. 2 After hot pressing for 10 minutes under the conditions of , the film was cooled to room temperature to obtain an electrolyte membrane 5 (thickness 100 μm) of Example 5. Table 1 shows the ratio (mol %) of the amount of cerium to the amount of ion exchange groups.
[0381] The membrane electrode assembly of Example 5 was obtained in the same manner as in Example 1 except that the electrolyte membrane 5 was used instead of the electrolyte membrane 1. It should be noted that the anode catalyst layer decal was bonded to the surface of the electrolyte membrane 5 on the electrolyte layer X7 side, and the cathode catalyst layer decal was bonded to the surface of the electrolyte membrane 5 on the electrolyte layer X1 side.
[0382] The membrane electrode assembly of Example 5 was subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0383] [Example 6]
[0384] The electrolyte layer X1 was used as the electrolyte membrane 6 (thickness 90 μm) of Example 6. Table 1 shows the ratio (mol %) of the amount of cerium substance to the amount of ion exchange group substance.
[0385] The membrane electrode assembly of Example 6 was obtained in the same manner as in Example 1 except that electrolyte membrane 6 was used instead of electrolyte membrane 1. The anode catalyst layer decal was bonded to one side of electrolyte membrane 6, and the cathode catalyst layer decal was bonded to the other side of electrolyte membrane 6.
[0386] The membrane electrode assembly of Example 6 was subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0387] [Example 7]
[0388] The electrolyte layer X1 and the electrolyte layer X6 were stacked and pressed using a flat plate press at 150° C. and a surface pressure of 30 MPa / m 2 After hot pressing for 10 minutes under the conditions of , the film was cooled to room temperature to obtain electrolyte membrane 7 (thickness 100 μm) of Example 7. Table 1 shows the ratio (mol %) of the amount of cerium to the amount of ion exchange groups.
[0389] The membrane electrode assembly of Example 7 was obtained in the same manner as in Example 1 except that the electrolyte membrane 7 was used instead of the electrolyte membrane 1. It should be noted that the anode catalyst layer decal was bonded to the surface of the electrolyte membrane 7 on the electrolyte layer X6 side, and the cathode catalyst layer decal was bonded to the surface of the electrolyte membrane 7 on the electrolyte layer X1 side.
[0390] The membrane electrode assembly of Example 7 was subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0391] [Table 1]
[0392]
[0393] In Table 1, the first electrolyte layer of Examples 1 to 5 is a general term for electrolyte layers containing a platinum-containing substance and cerium, and the second electrolyte layer is a general term for electrolyte layers not containing a platinum-containing substance and cerium.
[0394] As shown in Table 1, it was confirmed that the electrolyte membranes comprising a fluorinated polymer having an ion exchange group, a platinum-containing material, cerium, and a woven fabric had excellent low gas permeability and chemical durability (Examples 1 to 5).
[0395] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2022-145341 filed on September 13, 2022 are cited herein and incorporated as a disclosure of the specification of the present invention.
[0396] Description of Reference Numerals
[0397] 1, 10, 100 Electrolyte membrane
[0398] 20, 120 membrane electrode assembly
[0399] 22 Anode
[0400] 24 Cathode
[0401] 26 Catalyst layer
[0402] 28 Gas Diffusion Layer
[0403] 100A 1st electrolyte layer
[0404] 100B Second electrolyte layer
[0405] A1, C1 surface
[0406] B1 Depth Position
[0407] T1, T X distance
[0408] X, Y area
Claims
1. A solid polymer electrolyte membrane, characterized in that: Contains: fluorinated polymers with ion exchange groups, platinum-containing substances, cerium and fabrics, The cerium exists in the solid polymer electrolyte membrane in the form of at least one of an ion and a salt.
2. The solid polymer electrolyte membrane according to claim 1, wherein The platinum-containing substance and the cerium are concentrated on one surface side of the solid polymer electrolyte membrane.
3. The solid polymer electrolyte membrane according to claim 1, wherein The ion exchange capacity of the fluorine-containing polymer is 0.90 to 2.00 milliequivalents per gram of dry resin.
4. The solid polymer electrolyte membrane according to claim 1, wherein The platinum-containing material is loaded on a carrier.
5. The solid polymer electrolyte membrane according to claim 1, wherein The ion exchange group of the fluorine-containing polymer is a sulfonic acid type functional group.
6. The solid polymer electrolyte membrane according to claim 1, wherein The fluorinated polymer comprises at least one unit selected from the group consisting of a unit represented by formula (1-3) and a unit represented by formula (1-4), In formula (1-3) and formula (1-4), R f1 is a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f2 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f3 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, r is 0 or 1, m is 0 or 1, and M is each independently a hydrogen atom, an alkali metal or a quaternary ammonium cation.
7. The solid polymer electrolyte membrane according to claim 1, wherein The woven fabric is made of a material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyetheretherketone and polyphenylene sulfide.
8. The solid polymer electrolyte membrane according to claim 1, wherein The solid polymer electrolyte membrane comprises a first electrolyte layer and a second electrolyte layer. The first electrolyte layer includes the platinum-containing material and the cerium, The second electrolyte layer has a lower concentration of the platinum-containing substance and the cerium than the first electrolyte layer, or does not contain the platinum-containing substance and the cerium.
9. The solid polymer electrolyte membrane according to claim 1, wherein The thickness of the solid polymer electrolyte membrane is 80 μm or more, and the ratio of the amount of the cerium substance to the amount of the ion exchange group of the fluorine-containing polymer is 0.24 mol % or more.
10. A membrane electrode assembly, characterized in that: Include: The solid polymer electrolyte membrane according to any one of claims 1 to 9, a cathode catalyst layer disposed on one side of the solid polymer electrolyte membrane, and An anode catalyst layer is disposed on the other surface of the solid polymer electrolyte membrane.
11. A water electrolysis device, characterized in that: have: The membrane electrode assembly according to claim 10; a power supply unit connected to the cathode catalyst layer side and the anode catalyst layer side of the membrane electrode assembly; and A water supply unit supplies water to the anode catalyst layer side.
12. A method for manufacturing a membrane electrode assembly, the membrane electrode assembly comprising: the solid polymer electrolyte membrane according to any one of claims 1 to 9, a cathode catalyst layer and an anode catalyst layer, In the manufacturing method, the cathode catalyst layer is formed on one side of the solid polymer electrolyte membrane, and the anode catalyst layer is formed on the other side of the solid polymer electrolyte membrane.
Citation Information
Patent Citations
Novel microorganism with ability to reduce concentration of ammoniacal nitrogen in wastewater
JP2022145341A
Membrane electrode assembly, solid polymer electrolyte membrane, waer electrolysis system and electrolytic hydrogenation system
WO2022050363A1